Protein profiles in plasma: Development from infancy to 5 years of age. Issue 4 (2nd May 2021) - Mikus, Maria; Järnbert‐Pettersson, Hans; Johansson, Catharina; Nilsson, Peter; Scheynius, Annika; Alm, Johan
Abstract: Purpose: Little is known about the longitudinal development of different plasma protein levels during early childhood and particularly in relation to lifestyle factors. This study aimed to monitor the plasma proteome early in life and the influence of different lifestyles. Experimental Design: A multiplex bead‐based immunoassay was used to analyze plasma levels of 97 proteins in 280 blood samples longitudinally collected in children at 6, 12, 24, and 60 months of age living in families with an anthroposophic ( n = 15), partly anthroposophic ( n = 27), or non‐anthroposophic ( n = 28) lifestyle. Results: A total of 68 proteins (70%) showed significantly altered plasma levels between 6 months and 5 years of age. In lifestyle stratified analysis, 59 of 97 (61%) proteins were altered over time within one or more of the three lifestyle groups. Nearly half of these proteins (28 out of 59) changed irrespective of lifestyle. The temporal changes represented four longitudinal trends of the plasma proteins during development, also following stratification of lifestyle. Conclusions and Clinical Relevance: Our findings contribute to understand the development of the plasma proteome under the influence of lifestyle exposures in early childhood.